2022
DOI: 10.1136/bmjopen-2021-056896
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 pandemic responses in African countries: thematic synthesis of WHO intra-action review reports

Abstract: ObjectivesWe conducted a review of intra-action review (IAR) reports of the national response to the COVID-19 pandemic in Africa. We highlight best practices and challenges and offer perspectives for the future.DesignA thematic analysis across 10 preparedness and response domains, namely, governance, leadership, and coordination; planning and monitoring; risk communication and community engagement; surveillance, rapid response, and case investigation; infection prevention and control; case management; screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Country-led IARs have been conducted globally to assess several COVID-19 response domains (pillars) simultaneously, including a pillar for points of entry (PoE) [ 36 , 37 , 38 ]. IARs have also been implemented to focus specifically on countries’ COVID-19 response at PoE [ 39 , 40 ], with some IARs for ports and airports carried out under the European HEALTHY GATEWAYS framework [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Country-led IARs have been conducted globally to assess several COVID-19 response domains (pillars) simultaneously, including a pillar for points of entry (PoE) [ 36 , 37 , 38 ]. IARs have also been implemented to focus specifically on countries’ COVID-19 response at PoE [ 39 , 40 ], with some IARs for ports and airports carried out under the European HEALTHY GATEWAYS framework [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Communication challenges observed during the IAR reflect results of a study under the EU SHIPSAN project examining passenger ship hygiene inspection practices, where a lack of port-to-port communication was identified [ 48 ]. In a review of reports from COVID-19 IARs conducted in WHO African region countries until March 2021, the importance of appropriate information exchange between neighboring countries in the PoE context emerged [ 38 ]. COVID-19 revealed the importance of timely communication between ports in a cruise ship’s itinerary, including European and non-European countries.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency in the clinical case management (CM) capacities, in terms of unskilled staff, oxygen deficiency, therapeutics and treatments and medical equipment, was observed in the region at the onset of the pandemic. 25 To address the challenges, WHO, with the help of partners, has worked on the establishment of a regional stockpile of oxygen concentrators (800), oxygen cylinders (3800) and pulse oximeters (595) that are ready to be shipped to countries for urgent need. Regionally, more than 60 000 healthcare workers (HCWs) have been trained to manage critical and severe patients and the indications of rational oxygen use and other therapeutics and monitoring home-based and isolation care (HBIC).…”
Section: Progress On the Covid-19 Response In Who Africamentioning
confidence: 99%
“…To address the challenge, WHO and partners invested in training HCWs and 24 months into the pandemic had trained more than 12,000 medical officers and 44,000 nurses on COVID-19 treatment, surveillance standard operating procedures (SOPs), tools and guidelines across the region [ 26 ]. With the constant changing treatment protocols, many countries constantly updated their national treatment and therapeutics guidelines to include novel recommended COVID-19 therapeutics that arose as research developed in that area with the support of partners, as shown from the thematic analysis of WHO intra-action review reports [ 27 ]. Over the past two years, international emergency medical teams (EMTs) have been deployed to 25 countries where more than 6,000 HCWs have been trained [ 26 ].…”
Section: Progress Of the Covid-19 Response In Africamentioning
confidence: 99%